Effects of Adding Clove (Syzygium aromaticum L.) Seed Extract on Oxidative Stability, Microbial Activity, and Sensory Attributes in Beef Patties During Refrigerated Storage - Ahmed, Bestoon Hassan; Mohammed , Naska Abdulqadir Mohammed (Kurdistan Journal of Applied Research, 2024)
The study investigated the impact of clove seed extract (CSE) at concentrations of 0.20, 0.25, and 0.30% on the oxidative stability, microbial activity, and sensory quality of beef patties stored at 4°C for 10 days. The extract was obtained using ethanol (70%) and incorporated into the patties. Lipid oxidation was assessed through malondialdehyde (MDA) levels, microbial counts (aerobic plate count, coliform, and Pseudomonas spp. were recorded, and sensory evaluation measured color, taste, and overall acceptance. Results highlighted the effectiveness of 0.30% CSE in significantly reducing MDA levels, with values of 0.606 mg/kg compared to 0.657 mg/kg in the control group on Day 10. Microbial growth was inhibited in a concentration-dependent manner; for instance, aerobic plate counts decreased from 5.31 to 4.68 Log10 colony forming unit (CFU)/g, and coliform counts declined from 2.92 to 2.57 Log10 CFU/g at 0.30% CSE. Pseudomonas spp. also showed reduced numbers, stabilizing the patties' microbial quality. Sensory tests revealed that CSE-treated patties retained better color, flavor, and acceptability over time than untreated samples. Overall, the study concluded that 0.30% CSE significantly improved oxidative stability, inhibited microbial activity, and preserved sensory quality, thereby enhancing the shelf life of beef patties. These findings suggest that clove seed extract can serve as a natural, effective alternative to synthetic preservatives, promoting both product safety and consumer appeal.